2017
DOI: 10.1515/raon-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 130 patients with primary and secondary lung tumors treated with Cyberknife robotic stereotactic body radiotherapy

Abstract: Background Authors report clinical outcomes of patients treated with robotic stereotactic body radiotherapy (SBRT) for primary, recurrent and metastatic lung lesions.Patients and methods130 patients with 160 lesions were treated with Cyberknife SBRT, including T1-3 primary lung cancers (54%), recurrent tumors (22%) and pulmonary metastases (24%). The mean biologically equivalent dose (BED10Gy) was 151 Gy (72–180 Gy). Median prescribed dose for peripheral and central lesions was 3×20 Gy and 3×15 Gy, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
5
12
0
1
Order By: Relevance
“…In terms of local control, our results are close to what other studies have recently reported in the literature (3,(12)(13)(14).…”
Section: Discussionsupporting
confidence: 92%
“…In terms of local control, our results are close to what other studies have recently reported in the literature (3,(12)(13)(14).…”
Section: Discussionsupporting
confidence: 92%
“…The Cyberknife radiotherapy system has shown itself over the past decade to be a valuable method of delivering a high‐quality treatment, particularly for SBRT . One of its limitations is the long delivery time.…”
Section: Discussionmentioning
confidence: 99%
“…The Cyberknife radiotherapy system has shown itself over the past decade to be a valuable method of delivering a highquality treatment, particularly for SBRT. [21][22][23][24] One of its limitations is the long delivery time. For MLC treatments, this is because robot motion, MLC leaf motion, and beam-on are all largely performed in a serial fashion.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the Cyberknife system to treat from a variety of noncoplanar beam directions 27 is useful for high-quality treatment of SBRT. [1][2][3][4] Treating from such a range of orientations is time-consuming, so that the total treatment time is long. However, several recent studies have shown that use of a dynamic arc delivery can reduce the treatment time by a factor of approximately two.…”
Section: Discussionmentioning
confidence: 99%
“…The Cyberknife system (Accuray Inc., Sunnyvale, CA) has shown itself to be a valuable device for treating patients with stereotactic body radiotherapy (SBRT). [1][2][3][4] The short-waveguide 6-MV flattening-filter-free linear accelerator is mounted on a robotic arm and is equipped with either a series of circular collimators, a variable circular diaphragm, or a multileaf collimator (MLC). [5][6][7] The MLC is widely used to allow treatment of larger tumors using fewer monitor units.…”
Section: Introductionmentioning
confidence: 99%